Opportunistic Pathogen Porphyromonas gingivalis Modulates Danger Signal ATP-Mediated Antibacterial NOX2 Pathways in Primary Epithelial Cells - Roberts, JoAnn S.; Atanasova, Kalina R.; Lee, Jungnam; Diamond, Gill; Deguzman, Jeff; Hee Choi, Chul; Yilmaz, Özlem (Frontiers in Cellular and Infection Microbiology, 2017)
Porphyromonas gingivalis, a major opportunistic pathogen in the etiology of chronic periodontitis, successfully survives in human gingival epithelial cells (GECs). P. gingivalis abrogates the effects of a host danger molecule, extracellular ATP (eATP)/P2X7 signaling, such as the generation of reactive oxygen species (ROS) via the mitochondria and NADPH oxidases (NOX) from primary GECs. However, antimicrobial functions of ROS production are thoroughly investigated in myeloid-lineage immune cells and have not been well understood in epithelial cells. Therefore this study characterizes antibacterial NOX2 generated ROS and host downstream effects in P. gingivalis infected human primary GECs. We examined the expression of NOX isoforms in the GECs and demonstrate eATP stimulation increased the mRNA expression of NOX2 (p<0.05). Specific peptide inhibition of NOX2 significantly reduced eATP-mediated ROS as detected by DCFDA probe. The results also showed P. gingivalis infection can temporally modulate NOX2 pathway by reorganizing the localization and activation of cytosolic molecules (p47phox, p67phox, and Rac1) during 24 hours of infection. Investigation into downstream biocidal factors of NOX2 revealed an eATP-induced increase in hypochlorous acid (HOCl) in GECs detected by R19-S fluorescent probe, which is significantly reduced by a myeloperoxidase (MPO) inhibitor. MPO activity of the host cells was assayed and found to be positively affected by eATP treatment and/or infection. However, P. gingivalis significantly reduced the MPO product bactericidal HOCl in early times of infection upon eATP stimulation. Analysis of the intracellular levels of a major host-antioxidant, glutathione during early infection revealed a substantial decrease (p<0.05) in reduced glutathione indicative of scavenging of HOCl by P. gingivalis infection and eATP treatment. Examination of the mRNA expression of key enzymes in the glutathione synthesis pathway displayed a marked increase (p<0.05) in glutamate cysteine ligase (GCL) subunits GCLc and GCLm, glutathione synthetase and glutathione reductase during the infection. These suggest P. gingivalis modulates the danger signal eATP-induced NOX2 signaling and also induces host glutathione synthesis to likely avoid HOCl mediated clearance. Thus, we characterize for the first time in epithelial cells, an eATP/NOX2-ROS-antibacterial pathway and demonstrate P. gingivalis can circumvent this important antimicrobial defense system potentially for successful persistence in human epithelial tissues.